Overcoming Poverty and Socio-Territorial Differences: the Case of the Ethical Family Income in Chile - Fernández G., M. Ignacia (Revista del CLAD Reforma y Democracia, 2015)
Most Latin American countries have focused their policy efforts to overcome poverty in Conditional Cash Transfer programs (CCT). Nonetheless, it seems that these programs have fulfilled their cycle, as their capacity to effectively reduce poverty has been questioned. Research on the impact of CCT programs on household income and human capital is vast, however not much is known about their impact differentiated by territory. This work’s main argument is that factors that characterize different geographical territories may substantially change the local population’s capacity to capitalize incomes obtained by CCT. The article develops this idea in three ways: i) an analysis of local economic and institutional factors of two Chilean regions: Valparaíso and Los Ríos; ii) a panel study (2012-2014) on the evolution of income and assets of a group of beneficiaries of Chile’s Ethical Family Income (EFI) program; iii) an impact assessment of the IEF program in both regions. While Valparaíso shows a better socioeconomic performance than Los Ríos, there are no observable differences in regards to institutional performance. Considerable differences in income, physical capital and social capital were found among the beneficiaries of both regions: Valparaíso performs better in terms of both income and physical capital, Los Ríos shows better results in social capital. No significant impacts of EFI on human and social capital were found. The only significant impact found was a negative effect on autonomous income in Los Ríos, the region with the worse socioeconomic and labor conditions among the two. The article concludes on the importance of developing social intervention strategies according to different socioeconomic contexts, given its possible effect on the program’s impact on beneficiaries. There is no evidence to sustain this argument in regards to institutional conditions.